PENGARUH REPUTASI KANTOR AKUNTANSI PUBLIK, KUALITAS AUDIT DAN KEPATUHAN STANDAR AKUNTANSI KEUANGAN TERHADAP OPINI AUDIT PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022-2024 - Habibullah Habibullah; Martinus Budiantara (JURNAL ILMIAH EDUNOMIKA, 2026)
This study was conducted to determine the effect of public accounting firm reputation, audit quality, and compliance with financial accounting standards on audit opinions in energy sector companies listed on the Indonesia Stock Exchange for the 2022-2024 period. The population in this study was several companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period that had annual financial statements and independent auditor reports. The analysis tool used was SPSS. SPSS output shows that the reputation of the Public Accounting Firm (KAP) does not significantly influence the Audit Opinion (Y). Audit quality is measured by audit tenure, which is the length of the auditor-client relationship (the number of years the same auditor has audited the company). These results indicate that the length of the auditor-client relationship does not affect the audit opinion issued. Audit quality, measured by the length of the working relationship, is not sufficient to explain variations in audit opinions. Auditors are still considered to maintain independence, regardless of their long or new experience with the client, with audit tenure having no significant effect on the audit opinion. Compliance with Financial Accounting Standards (SAK) significantly influences the Audit Opinion (Y).